Probing secondary school students' test anxiety in biology using Inquiry-based instructional approach in Anambra State - Nwuba, Izunna; Mmodum, Isaac-Martin C.; Agwuna, Cynthia C.; Mbaegbu, Chioma S.; Egwu, Sussan O.; Awosika, Opeyemi F. (Papanda Publisher, 2024)
The study investigated the effect of inquiry-based instructional approach (IBIA) on secondary school students’ test anxiety in biology. The study is a quasi-experimental research, adopting specifically the non-randomized control group design. 4,755 (2,067 males and 2,688 females) Senior Secondary year two (SS2) students offering biology in the 62 government owned secondary schools, in Awka Education Zone of Anambra State, Nigeria constituted the population. 52 (20 males and 32 females) SS2 biology students drawn from, two intact classes, in the two sampled schools, using multi-stage sampling procedure constituted the sample size. The instrument for data collection was an adapted Biology Test Anxiety Scale (BTAS), validated by three experts with reliability coefficient of 0.78 established using Cronbach Alpha. In analyzing the collected data, mean and standard deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was employed to test the null hypotheses. The findings revealed that students taught biology with IBIA significantly showed low test anxiety in biology than those taught with the conventional lecture method, irrespective of gender. Based on the findings, the study concluded that IBIA is a gender friendly, activity-based approach that boosts students’ confidence, and promotes meaningful learning in biology. In light of this, it was recommended among others that IBIA should be adopted by biology teachers in secondary schools to actively engage students in the learning process which will in return help boost their confidence during tests and thus, reduce their anxiety.